ISOBARIC LEVOBUPIVACAINE VERSUS HYPERBARIC BUPIVACAINE IN PREGNANT WOMEN UNDERGONE CESAREAN SECTIONS: A RANDOMIZED CONTROLLED TRIAL - AMJAD, A; SADIA, H; SAAD, M; ALI, A; NAEEM, A; NAEEM, H; AHMED, M (Biological and Clinical Sciences Research Journal, 2023)
To compare isobaric levobupivacaine versus hyperbaric bupivacaine for pregnant women who have undergone cesarean sections. In this randomized controlled trial, 70 patients with ASA physical status I-II, scheduled i.e for elective lower segment cesarean section (LSCS), were divided into two equal-sized groups (n = 35 each). Group A was treated with 2.5 ml of isobaric levobupivacaine, while Group B was treated with 2.5 ml of hyperbaric bupivacaine. Both groups' sensory and motor block features were evaluated using the pinprick test and the Bromage scale. Additionally, any instances of hypotension and potential side effects were meticulously recorded. Subsequently, the collected data underwent statistical analysis employing appropriate tests. The initiation of sensory blockage was observed to be slower, and the regression duration for two segments was extended while using isobaric levobupivacaine (p < 0.001). Nevertheless, it generated sufficient surgical anesthetic with a reduced duration of motor blocking and fewer side effects compared to hyperbaric bupivacaine. This study concludes that single-shot spinal anesthesia with different local anesthetics is effective for prompt surgical anesthesia induction in elective cesarean section procedures. Among these options, levobupivacaine is a superior choice due to its smaller duration of motor block, reduced side effects, and lower risk of hypotension, making it particularly well-suited for such procedures.